Kokoru paper craft training to improve students’ skills of SDN Cintalaksana 1 Karawang - Qur’aeni, Asyifa Lu’lu; Fuada, Syifaul; Herlinawati, Heni (Community Empowerment)
Cintalaksana 1 Elementary School Karawang, West Java applies a limited online and offline learning model during the Covid-19 pandemic. Some students feel bored because the hybrid learning is still monotonous. Arts, Culture and Crafts (SBdP) subjects can be optimized to overcome student boredom, because in addition to very entertaining/fun learning, they can also explore, hone, and develop the potential of students. As an implication, students' enthusiasm for learning can increase. SBdP learning with interesting materials can increase students' creativity during a pandemic and can even generate economic value. Based on the problems found, a craft training from kokoru paper was held which aims to increase students' creativity while at the same time making SBdP subjects more varied. The methods of implementing the training include: 1) planning; 2) training held offline by implementing strict health protocols; and 3) evaluation. The results show that students are skilled at making kokoru according to the shape or object they want by only looking at examples of existing products and knowing the manufacturing techniques which tend to be very easy, namely folding, rolling, cutting, pasting, and decorating with knick-knacks. Participants gave a positive response after participating in the activity, they could fill their boredom while studying during the pandemic with a new hobby. Kokoru can be applied to increase student creativity through SBdP subjects, especially paper-based handicrafts.